The Effect of Managerial Skills (Conceptual, Human, and Technical) of Headmasters to the Effectiveness of Islamic Senior High Schools in Jombang District - Mukarromah, Ilzamatul; Mudjito, Mudjito; Purbaningrum, Endang (International Journal for Educational and Vocational Studies, 2019)
This study aims to determine the effect of managerial skills of a headmaster to the effectiveness of islamic senior high school in Jombang District. This research is a quantitative study with a type of survey approach. Data were collected by distributing questionnaires to 100 respondents, namely teachers from 4 islamic senior high schools in Jombang District as samples of this study. The research data were obtained from a questionnaire containing 45 statements regarding managerial skills and school effectiveness. The results of this study found that managerial skills of a headmaster affected school effectiveness. The results of the test of the individual parameters significance state that managerial skills (conceptual, human, and technical) are respectively influential by 72%, 75%, and 62% on school effectiveness. Meanwhile, simultaneously managerial skills have an effect of 77% on school effectiveness.